A Review of Life Science Studies with Muons - Pant, A. D. (Journal of Nepal Physical Society, 2021)
Positive muon is a spin half elementary particle lies in the second generation leptons in standard model of particles. It has been used as a sensitive magnetic (spin) probe for study of life and materials. Due to its special characteristics – 100% polarization and asymmetric decay to positron, it provides information about local electronic and spin states of material in which it stops. The asymmetry, relaxation of muon and its charge states in materials provide information about the interested phenomena. For life sciences study, muon can probe the dynamics of electron, proton, ions, H, O2, reaction dynamics, catalytic processes, concentration of molecules, magnetic behaviors, etc. in the biosamples. Here, the applications of positive muon to understand the life related phenomena are reviewed.